A "Sloppy Wet Kiss"? Intralingual Translation and Meaning-Making in Contemporary Congregational Songs - Thornton, Daniel (Religions, 2021)
Translation as a form of music localization does not only occur in diverse cultural or lingual contexts, it also occurs within an ostensibly homogenous culture and language. The global genre of contemporary congregational songs (CCS) is written and performed through a variety of theological lenses. Sometimes a theological position conveyed in, or ascribed to, CCS can be problematic for certain local expressions of the Christian faith to replicate without needing to alter lyrics, and/or musical content, or at least reinterpret those lyrics in a way which aligns with their theological understanding. This article explores popular CCS, as measured by Christian Copyright Licensing International (CCLI) which have been either accepted, rejected, reinterpreted, or otherwise altered in order to play their part in defining local (English-speaking) church worship and identity. Translation studies and music semiology are applied to selected CCS to demonstrate this nuanced interpretation of "translation" in the localizing of religious musical practice